Pengetahuan Ditinjau dalam Perspektif Posmodernisme - Alwen Bira (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
Postmodernism cannot be separated from modernism. Modernism's paradigm that science is absolute and objective means that humans cannot judge it. This is where a new thought called postmodernism was born which became a continuation of modernism which gave a new view of science. This study uses a type of qualitative research with hermeneutic methods, descriptions and comparisons to answer the problem. The conclusion of this study shows that postmodernism is a movement that criticizes science for the tradition of modernism whose influence on rationalism, materialism and capitalism is supported by science and destroys human dignity. Postmodernism emerged due to the failure of modernism which raised human dignity and failed to bring human life to a better direction, free from violence.